Pemanfaatan Pewarna Alam sebagai Trend Baru pada Fashion Brands di Indonesia - Arini Arumsari; Agus Sachari; Andryanto Rikrik Kusmara (JURNAL RUPA, 2018)
As one of the largest sub-sectors of the creative industry in Indonesia, the fashion industry has a great potential and contribution to society and the country's economy. However, the role of the large fashion industry also needs to be balanced with the methods of production and design of fashion products that are environment-friendly. This needs to be done considering the potential for adverse impacts of the rapidly developing fashion industry without any direction. The adverse effects are the use of synthetic materials or raw materials that are harmful to the environment; unprocessed production waste; poor quality of materials and production processes resulting in a low product life-cycle; and social labor issues. To overcome the above problems, the environment-friendly method currently used by various fashion brands in Indonesia and becoming a trend is the use of natural dyes in the process of fashion production. The use of natural dyes has many advantages, namely: using non-toxic and dangerous materials; preserving the traditions of Indonesian ancestors; and producing authentic and trendy color characters if processed properly. This study uses qualitative methods with a sociocultural approach. This study presents the background and development of the use of natural dyes by various fashion brands in Indonesia to become today's trend. Thus, the use of natural dyes is expected to not only become a momentary trend but is also expected to continue to be developed. The biggest reason is that the application of more environment-friendly methods for the Indonesian fashion industry broadly can provide many benefits.